N‐Terminal Modification of Proteins with Subtiligase Specificity Variants. Issue 1 (19th February 2020) - Weeks, Amy M.; Wells, James A.
Abstract: Subtiligase is a powerful enzymatic tool for N‐terminal modification of proteins and peptides. In a typical subtiligase‐catalyzed N‐terminal modification reaction, a peptide ester donor substrate is ligated onto the unblocked N terminus of a protein, resulting in the exchange of the ester bond in the donor substrate for an amide bond between the donor substrate and protein N terminus. Using this strategy, new chemical probes and payloads, such as fluorophores, affinity handles, cytotoxic drugs, and reactive functional groups, can be introduced site‐specifically into proteins. While the efficiency of this reaction depends on the sequences to be ligated, a panel of mutants was recently developed that expands the scope of substrate sequences that are suitable for subtiligase modification. This article outlines the steps for applying subtiligase or specificity variants for both site‐specific bioconjugation of purified proteins and for global modification of cellular N termini to enable their sequencing by tandem mass spectrometry. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Subtiligase‐catalyzed site‐specific protein bioconjugation Support Protocol 1 : Expression and purification of subtiligase‐His6 Support Protocol 2 : Subtiligase substrate synthesis Basic Protocol 2 : Subtiligase N terminomics using a cocktail of subtiligase specificity mutants